2013
DOI: 10.1186/1479-5876-11-114
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear β-catenin accumulation is associated with increased expression of Nanog protein and predicts poor prognosis of non-small cell lung cancer

Abstract: BackgroundAlthough the prognostic roles of β-catenin expression in non-small cell lung cancer (NSCLC) have been reported in several immunohistochemical (IHC) studies, the results were not consistent because some studies lack sufficient number of the positive cases or did not evaluate the subcellular localization features of the protein.MethodIn this study, we have evaluated the expression levels and subcellular localization of β-catenin and Nanog proteins IHC staining in tissue specimens from 309 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 32 publications
4
65
0
Order By: Relevance
“…We found that IL-35 was expressed in non-tumor tissues and it was down- progression [21]. To gain further insight into the role of IL-35 in NSCLC, we examined the expression of β-catenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that IL-35 was expressed in non-tumor tissues and it was down- progression [21]. To gain further insight into the role of IL-35 in NSCLC, we examined the expression of β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of β-catenin in A549 and SK-MES-1 cells were analyzed after treatment with 100 ng/mL rhIL-35 for 24 h, because of the important role of β-catenin in NSCLC development [21]. The mRNA and protein levels of β-catenin were suppressed by IL-35 in these two cell lines (Fig.…”
Section: Il-35 Inhibits β-Catenin Expression In Nsclc Cellsmentioning
confidence: 99%
“…For the immunohistochemical detection of β-catenin, the sections were stained with a human monoclonal antibody to β-catenin (1:200, Cell Signaling Technology). Lung cancer tissues, known to widely express β-catenin, 6,23,24 were used as positive control. The immunostaining pattern in the epithelium of airways was blindly evaluated by two investigators.…”
Section: Lung Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…We know that the β-catenin gene is upstream of Nanog, Oct3/4, Sox2, c-Myc, and Klf4, and our previous studies have shown that there is a correlation between β-catenin and Nanog in lung cancer (31,32). Moreover, elevated β-catenin expression can promote Nanog, Oct3/4, Sox2, c-Myc, and Klf4 expression (33,34).…”
Section: Discussionmentioning
confidence: 94%